2019
DOI: 10.1186/s12934-019-1110-4
|View full text |Cite
|
Sign up to set email alerts
|

Construction of DGLA producing cell factory by genetic modification of Mucor circinelloides

Abstract: Background Dihomo-gamma linolenic acid (DGLA, 20:3, n-6) is the elongated product of Gamma linolenic acid (GLA, 18:3, n-6) catalyzed by the enzyme delta-6 elongase (D6E) or gamma linolenic acid elongase (GLELO). Construction of engineered oleaginous microbes have been attracting significant interest to produce DGLA because of its nutritional value and medicinal applications. Mucor circinelloides is a GLA producing filamentous fungus which can be a useful tool to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…In the present study after 48 h of cultivation, pigment production started to decline under light and dark conditions. This decline in β-carotene could be attributed to maximum lipid accumulation phase that is 72 h of cultivation as reported in our study and reported by [35] in M. circinelloides. It is well known fact that in M. circinelloides, FAS and mevalonate pathway shares the same acetyl-CoA pool, so it is speculated that after 48 h, more acetyl-CoA was diverted toward lipid metabolism as compared to carotenoid biosynthesis in our study.…”
Section: Yield Of Biomass β-Carotene and Lipid By Cbs 27749 And Wjsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study after 48 h of cultivation, pigment production started to decline under light and dark conditions. This decline in β-carotene could be attributed to maximum lipid accumulation phase that is 72 h of cultivation as reported in our study and reported by [35] in M. circinelloides. It is well known fact that in M. circinelloides, FAS and mevalonate pathway shares the same acetyl-CoA pool, so it is speculated that after 48 h, more acetyl-CoA was diverted toward lipid metabolism as compared to carotenoid biosynthesis in our study.…”
Section: Yield Of Biomass β-Carotene and Lipid By Cbs 27749 And Wjsupporting
confidence: 86%
“…Biomass was harvested on a dried and pre-weighed filter paper by filtration through a Buchner funnel under reduced pressure and washed three times with distilled water, frozen overnight at −80 • C and then freeze-dried. The weight of the biomass was determined gravimetrically [35].…”
Section: Cell Dry Weight Determination (Cdw)mentioning
confidence: 99%
“…Finally, the fatty acid methyl esters (FAMEs) were extracted with n-hexane and subsequently analyzed by GC using the DB-Waxetr column with the following specifications: film thickness 0.25 µm, 30 m×0.32 mm (Shimadzu Co., Ltd., Kyoto, Japan). The program used for the gas chromatography (GC) was as follows: 120 • C for 3 min, ramp to 200 • C at 5 • C min −1 , ramp to 220 • C at 4 • C min −1 , and hold for 2 min [1,33].…”
Section: Total Lipid and Fatty Acid Profilingmentioning
confidence: 99%
“…Mucor circinelloides is regarded as a model organism for investigations of lipid accumulation. It has been extensively genetically manipulated for the production of diverse biotechnological precursors for the functional food and bio-fuel industries [1,33,34]. However, its fatty acid profile indicates that it is mostly formed by long-chain fatty acids (LCFAs), ultimately making it less attractive for multi-purpose industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of infections associated with Mucor species, as well as the biotechnological potential of the genus, have led to a large effort to better know these fungi. In this context, Vongsangnak et al proposed a metabolic network of the oleaginous strain Mucor circicinelloides WJ11 [10,11], Corrochano et al shed new light on Mucor sensory perception [12], and multiple genes potentially involved in virulence were investigated and discovered in Mucor spp. [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%